2018
DOI: 10.12928/ijeme.v2i1.8670
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Derivatives by Means of GeoGebra

Abstract: Tulisan ini bertujuan untuk menjelaskan bagaimana GeoGebra dapat digunakan dalam pembelajaran kalkulus untuk mengeksplorasi konsep derivative dengan menyediakan visualisasi yang dinamis pada konsep tersebut. Penelitian desain digunakan dalam penelitian ini dengan menyusun instruksional desain (hipotesis lintasan belajar) pada tahap pertama dilanjutkan dengan melaksanakan eksperimen mengajar pada tahap kedua. Data yang diperoleh saat eksperimen berlangsung terdiri dari video rekaman, hasil observasi, interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, the connections of different representations and meanings are those that report the previous research that students and teachers do little and therefore, lead them to present difficulties in solving problems (Berry y Nyman, 2006;Hashemi et al, 2014;Moru, 2020;Pino-Fan et al, 2015;Pino-Fan et al, 2017;Sari et al, 2018;Ubuz, 2007). The mathematical connections of meanings of the derivative (slope of the tangent line to a curve at a point and limit of the incremental quotient) were the most evident, and connections between multiple representations of the derivative also emerged in the written productions of the participants, which in the study by Sari et al (2018) they are presented as difficult to do. Also, in the mathematical connections of meaning the part-whole connection was inferred, since only two meanings that belong to a global meaning of the derivative reported in the study of Font (2011) andPino-Fan (2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the connections of different representations and meanings are those that report the previous research that students and teachers do little and therefore, lead them to present difficulties in solving problems (Berry y Nyman, 2006;Hashemi et al, 2014;Moru, 2020;Pino-Fan et al, 2015;Pino-Fan et al, 2017;Sari et al, 2018;Ubuz, 2007). The mathematical connections of meanings of the derivative (slope of the tangent line to a curve at a point and limit of the incremental quotient) were the most evident, and connections between multiple representations of the derivative also emerged in the written productions of the participants, which in the study by Sari et al (2018) they are presented as difficult to do. Also, in the mathematical connections of meaning the part-whole connection was inferred, since only two meanings that belong to a global meaning of the derivative reported in the study of Font (2011) andPino-Fan (2013).…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, students have difficulty connecting and use multiple representations (graphic, symbolic, etc. ) of the derivative (Kula-Ünver, 2020;Pino-Fan, Godino & Font, 2015;Sánchez-Matamoros, Fernández & Llinares, 2015;Sari, Hadiyan & Antari, 2018). Also, in another study on understanding the derivative some students stayed at the inter-level since it is difficult for them to relate the function f with its derivative and they graph the derivative f' similar to the function f (Borji, Font, Alamolhodaei & Sánchez, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that students establish mathematical connections between multiple representations of the derivative, a situation that is difficult in the research of Sari et al (2018) and in the study of Hashemi et al (2014). We highlight the work done by S3 where he made mathematical connections of implication type (quality level 2) to graph considering the information provided by '.…”
Section: Discussionmentioning
confidence: 96%
“…Hashemi et al (2014) reported that students have limited conceptual understanding of the derivative, due to the poor connection between algebraic and graphical aspects. Likewise, students have difficulty connecting multiple representations of the derivative (Sari et al, 2018). Borji et al (2018) reported that the majority of the students stayed at the inter level since it is difficult for them to relate the function with its derivative and graph the derivative ' similar to the function .…”
Section: / 21mentioning
confidence: 99%
“…[13] GeoGebra software is open-source software. [14] It is structured software. [15] GeoGebra software has a friendly interface, easy to use.…”
Section: Overview Of Geogebra Softwarementioning
confidence: 99%